Strategy for Increasing Human Resources Through Infrastructure - Ali Mashari; Astiti Amalia; Meilinda Safitri; Dermawan Waruwu (EDUKASI : Jurnal Pendidikan Islam (e-Journal), 2023)
Human resource management is a process closely related to implementing management strategies that are directly handed over to schools to be developed according to their potential. The purpose of this study is to describe the strategy for the development and quality of human resources in elementary schools. This research is a type of field study or qualitative, collecting data according to the phenomena at the location, namely at Muhammadiyah Al-Birru Ponorogo. Data collection techniques through observation during meeting activities between leaders and subordinates, interviews with school principals, committee members, foundation members and stakeholders, documentation of assignment letters, photos of activities. The results showed: that a well-planned human resources improvement strategy is a benchmark for the maximum success or failure of human resources management by developing the potential of human resources who have their respective talents directed according to the knowledge of the teachers and healthy competition between human resources with the stimulus of giving awards to educators. Implementation of improving human resource educators through periodic semester career coaching, maximizing IT class management, and learning innovation with collaborative teaching methods. The success of improving school human resources very influential in carrying out the learning process properly and perfectly organized.